Penguatan Kesadaran Hukum Masyarakat Pesisir Tentang Perlindungan Mangrove Sebagai Upaya Mitigasi Bencana Alam Di Desa Sugian, Kecamatan Sambelia, Kabupaten Lombok Timur - Nathania Permata S; Hera Alvina S; Ika Yuliana Susilawati; Lalu Panca Tresna D; Yuni Ristanti (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Mangrove ecosystems play a strategic role in maintaining the balance of coastal environments and supporting the sustainability of community economies. However, in Sugian Village, Sambelia Subdistrict, East Lombok Regency, the existence of mangroves faces threats due to the low level of legal awareness among the community in preserving and protecting the environment. The main problem identified is the limited public understanding of mangrove protection regulations and the low level of active participation in conservation efforts. This community service activity aims to enhance public legal awareness and understanding through educational and participatory legal counseling. The methods used include socialization, interactive discussions, and a local wisdom–based approach. The results of the activity indicate an increase in community understanding of the importance of mangrove protection, both from legal and ecological perspectives. The community has begun to recognize the strategic role of mangroves in preventing coastal abrasion, maintaining biodiversity, and supporting livelihoods. Sustained efforts are needed to ensure long-term behavioral change within the community. Therefore, synergy between the government, academics, and the community is essential to strengthen legal awareness and encourage active participation in mangrove conservation.